Preparation method of silver-carbon nanoparticle and full-bagasse-based silver-carbon preservative film

By using sugarcane wood quality and phenylramine to prepare nitrogen doped carbon dots, and compound with silver nitrate, formed silver -carbon nanoparticles@cellulose composite material, solving the production of harmful substances in the existing silver -based fresh -keeping materials and nano -silver The problem of fast granular release achieves efficient mitigation and synergistic antibacterial effects.

CN119371718APending Publication Date: 2025-01-28GUANGXI UNIV FOR NATITIES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411606237.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

There are harmful substances produced during the preparation of existing silver-based fresh preservation materials, and the nano silver particles are released quickly and stored for a short time, which cannot effectively achieve sustained release and coordinated antibacterial.

Method used

The quality of sugarcane dregs and phenylramine is used to prepare nitrogen doped carbon dots (N-CQDS) through water heat reactions, and mixes ultrasound with silver nitrate to form silver-carbon nanoparticles@cellulose composite material to achieve in situ reduction and Slow release.

Benefits of technology

The slow release of silver -carbon nanoparticles has been realized, and the characteristics of antibacterial synergy are avoided, avoiding the generation of harmful substances, and improving the effect of food preservation and human health and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371718A_ABST
    Figure CN119371718A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of silver-carbon nanoparticles and a full-bagasse-based silver-carbon preservative film, and the preparation method of the silver-carbon nanoparticles comprises the following steps: extracting lignin from bagasse, dissolving the lignin and phenylenediamine in an acid solution, treating to obtain a reaction solution, centrifuging, taking supernate, dialyzing to obtain lignin nitrogen-doped carbon dots, and drying the lignin nitrogen-doped carbon dots to obtain the full-bagasse-based silver-carbon preservative film. Mixing the lignin nitrogen-doped carbon dots with deionized water to obtain an N-CQDs solution, mixing the N-CQDs solution with a silver nitrate solution for reaction, and then cooling, centrifuging, dialyzing and drying to obtain silver carbon nanoparticle powder; meanwhile, bagasse with lignin removed is taken to be subjected to TEMPO treatment and filtered, filter residues, an N-CQDs solution and an AgNO3 solution are mixed and react to obtain feed liquid, then the feed liquid is added into an aqueous solution containing glycerinum and formamide to react, and the full-bagasse-based silver-carbon preservative film is prepared. The defects of an existing silver-based fresh-keeping material are overcome, the fresh-keeping material is environmentally friendly and has the efficient synergistic antibacterial characteristic, and high-value utilization of the waste bagasse is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano antibacterial materials, and in particular relates to a method for preparing silver-carbon nanoparticles and a whole bagasse silver-carbon cling film. Background Art

[0002] Silver-based packaging is a promising technology for preserving fruits. However, the traditional preparation process of silver-based materials is accompanied by the production of harmful substances, and silver nanoparticles (AgNPs) have problems such as fast release and short shelf life. Therefore, it is very important to explore a green in-situ reduction method for preparing silver-based preservative materials using biomass materials.

[0003] Lignin contains abundant reducing functional groups in its molecular structure, which can be used as a reducing agent for preparing silver nanoparticles. However, the silver nanoparticles prepared in this way are not easy to disperse, lack dispersing protective agents and are easy to accumulate. Further preparing lignin into carbon nanodots (Cdots) is an effective method. A large number of studies have shown that Cdots can regulate silver nanoparticles and form synergistic antibacterial agents with silver nanoparticles. However, the existing technology has prepared linear AgNPs / CDs and carbon sphere-coated silver nanoparticle structures, but they either have low fixation efficiency or do not have synergistic antibacterial properties and require additional reducing agents. For example, linear silver carbon nanoparticles cannot achieve sustained release of silver nanoparticles, and although the fixation efficiency of silver nanoparticles coated with carbon spheres is improved, due to the large size of the carbon spheres themselves, they do not have antibacterial properties and cannot exert synergistic antibacterial properties with silver nanoparticles. Summary of the invention

[0004] In view of the above-mentioned shortcomings, the present invention discloses a method for preparing silver-carbon nanoparticles and a whole bagasse silver-carbon preservative film, which solves the problems that harmful substances exist in the preparation process of existing silver-based preservative materials, which is not conducive to food preservation and human health, and the preservative material has good sustained-release effect and efficient synergistic antibacterial properties.

[0005] The present invention is achieved by adopting the following technical solutions: A method for preparing silver-carbon nanoparticles comprises the following steps: (1) Add bagasse to sodium hydroxide solution, heat and stir for 10-15 hours, filter to obtain black liquor, and then acidify the black liquor to obtain lignin; (2) dissolving the lignin and phenylenediamine obtained in step (1) in an acid solution, placing the mixture in a polytetrafluoroethylene-lined autoclave, treating the mixture at 200° C. for 10 h, and then cooling the mixture naturally to room temperature to obtain a reaction solution; The acid solution is obtained by mixing sulfuric acid and phosphoric acid, and the volume ratio of the sulfuric acid to the phosphoric acid is 40:60; (3) After centrifuging the reaction solution obtained in step (2), the supernatant was dialyzed in deionized water for 48 hours to retain the molecular weight of 1000 Da, and then dried to obtain lignin nitrogen-doped carbon dots; (4) taking the lignin nitrogen-doped carbon dots obtained in step (3) and adding deionized water to obtain an N-CQDs solution, then mixing the N-CQDs solution with a silver nitrate solution and ultrasonicating the mixture, and then placing the mixture in an oil bath at 80° C. for 12 h to obtain a mixed solution; (5) The mixed solution obtained in step (4) was naturally cooled to room temperature and then centrifuged. The precipitate was dialyzed in a 1000Da dialysis bag for 48 hours and then dried at 80 °C to obtain silver carbon nanoparticle powder.

[0006] The present invention forms a silver-carbon nanoparticle@cellulose composite material in situ by combining lignin carbon dots with silver nitrate and bagasse cellulose. The carbon dots retain some properties of the precursor, so the lignin carbon dots have reducing and antibacterial properties. In order to form a composite structure with the reduced silver nanoparticles, the present invention modifies the lignin carbon dots and prepares nitrogen-doped carbon dots (N-CQDs) by doping lignin with amino groups.

[0007] Furthermore, the pH value of the sodium hydroxide solution in step (1) is 13.

[0008] Furthermore, the acid precipitation in step (1) is to add 1M sulfuric acid to the black liquor to adjust the pH value to 2, and then filter to obtain lignin.

[0009] Furthermore, in step (3) and step (5), the centrifugation is performed at a speed of 8000 to 10000 r / min for 15 to 20 min.

[0010] Furthermore, in step (4), the volume ratio of the N-CQDs solution to the AgNO3 solution is 5:4; the concentration of the N-CQDs solution is 2.5-10 mg / mL, and the concentration of the silver nitrate solution is 0.5-2.0 mol / L.

[0011] A method for preparing a full bagasse-based silver-carbon cling film comprises the following steps: S1, taking bagasse, adding it to sodium hydroxide solution, heating and stirring for 10-15h, and then filtering to obtain black liquor and filter residue; S2, bleaching the filter residue obtained in step S1, and then immersing it in treatment solution A, then adding sodium hypochlorite solution, and using oil bath method, reacting at 28-35° C. for 10-15 hours, then filtering to obtain cellulose, and storing the cellulose in deionized water to obtain a cellulose solution for standby use; The treatment liquid A comprises the following components in parts by weight: 0.030-0.035 parts of TEMPO (2,2,6,6-tetramethylpiperidin-1-oxyl free radical), 2.0-2.5 parts of sodium chlorite, 7-8 parts of sodium phosphate, and 180-220 parts of deionized water; the volume ratio of the added sodium hypochlorite solution to the treatment liquid A is 1:(8-12); S3, adding the lignin nitrogen-doped carbon dots (N-CQDs) obtained by the above preparation method to deionized water to obtain an N-CQDs solution, then mixing the N-CQDs solution with an AgNO3 solution to obtain a treatment solution B, then mixing the treatment solution B with the cellulose solution obtained in step S2, and then heating and reflux at 80 ° C for 12 to 24 hours to obtain a feed solution; the volume ratio of the N-CQDs solution to the mass ratio of the bagasse in step S1 is 25 mL: 1 g, and the volume ratio of the N-CQDs solution to the AgNO3 solution is 5:4; S4, cooling the liquid obtained in step S3, then repeatedly filtering three times, taking the filtered residue and adding it to the treatment liquid B to react for 1 hour, and then ultrasonicating for 1 hour and then air-drying at 40°C to obtain a full bagasse-based silver-carbon preservative film; the treatment liquid B is obtained by mixing glycerol, formamide and deionized water.

[0012] Similar to the in-situ formation of silver-carbon nanoparticle composite structures by lignin nitrogen-doped carbon dots and silver nitrate, the present invention further introduces bagasse (TEMPO-treated cellulose) with lignin removed to further regulate silver-carbon nanoparticles and synergistically reduce silver ions. The reductive C6 hydroxyl functional groups and reactive sites in the chemical structure of cellulose are sufficient for in-situ reduction of silver nanoparticles. At the same time, the present invention realizes the high-value utilization of various components of waste bagasse. A "bayberry hanging branch" bionic structure (AgC@MC) with carbon dots coated with nanosilver on fibers can be constructed in situ by using waste bagasse cellulose, waste bagasse lignin nitrogen-doped carbon dots, and silver nitrate.

[0013] In addition, traditional fresh-keeping materials have problems in recycling and degradation. Cellulose, as a natural substance, has many excellent properties, such as biodegradability, biocompatibility and good film-forming properties, and can be used as a film-forming substrate for silver-based antibacterial materials. The present invention releases silver slowly by adding carbon dots and cellulose. It is worth noting that the carbon dots obtained by the present invention are part of the intelligent response. When the composite film is exposed to light, the carbon dots will release superoxide radicals to synergistically resist bacteria.

[0014] Furthermore, in step S2, the concentration of the N-CQDs solution is 2.5 to 10 mg / mL, and the concentration of the silver nitrate solution is 0.5 to 2.0 mol / L.

[0015] Furthermore, the bleaching in step S2 is to first add glacial acetic acid to a bleaching agent to adjust the pH value to 4.6, and then put the filter residue obtained in step (1) into the bleaching agent for bleaching, the mass ratio of the filter residue to the volume of the bleaching agent is 2g:500mL, and the bleaching agent is a sodium chlorite aqueous solution with a concentration of 1.2-1.3g / mL.

[0016] Furthermore, after the filter residue in step S2 is bleached, it is rinsed with deionized water and filtered until the pH is neutral.

[0017] Furthermore, in step S3, the mass ratio of glycerol to formamide in the treatment liquid B is 7:3.

[0018] Compared with the prior art, this technical solution has the following beneficial effects: 1. The linear AgNPs / CDs and carbon ball-coated silver nanoparticle structures prepared by the prior art either have low fixation efficiency or do not have synergistic antibacterial properties, and an additional reducing agent is required during the preparation process. For example, linear silver-carbon nanoparticles cannot achieve sustained release of silver nanoparticles, and although the fixation efficiency of carbon ball-coated silver nanoparticles is improved, due to the large size of the carbon balls themselves, they do not have antibacterial properties and cannot play a synergistic antibacterial role with silver nanoparticles. The present invention uses raw materials such as bagasse lignin and o-phenylenediamine to prepare carbon dots with high light response, high antibacterial and high fixation rate through hydrothermal reaction. Thanks to the antibacterial property and fixation efficiency improved by amino doping, the prepared silver-carbon nanocomposite material has a good sustained release effect and efficient synergistic antibacterial properties. After being compounded with bagasse cellulose, a bionic structure of "bayberry hanging branches" is formed, which realizes the dual fixation of silver nanoparticles, and the sustained release capacity is greatly improved, especially the long-term synergistic antibacterial without the production of harmful substances.

[0019] 2. The present invention uses bagasse lignin carbon dots and bagasse cellulose to be greenly prepared by one-step in-situ reduction of silver carbon nanoparticles (AgC) and all-bagasse-based silver carbon cling film (AgC@MC) (a bionic structure similar to "bayberry hanging branches") to achieve synergistic antibacterial, reduction and fixation of silver ions. Among them, the nitrogen-doped carbon dots prepared by discarded bagasse lignin have antibacterial properties with enhanced light response, and the lignin carbon dots are evenly dispersed on the surface of the silver nanoparticles to form a carbon layer, which not only plays a synergistic antibacterial role but also slowly releases silver ions. The abundant polar functional groups in cellulose can further fix the silver carbon nanoparticles through hydrogen bond interactions, achieving the effect of dual fixation of silver nanoparticles, and even the abundant reducing functional groups on the surface of cellulose can cooperate with the lignin carbon dots to reduce silver ions in situ. In addition, the cellulose in bagasse has excellent film-forming ability and can form a uniform and stable film. Its good hygroscopicity can be used to adjust the humidity of the material, thereby performing well in food preservation and carrier release. At the same time, bagasse cellulose is a renewable resource, biodegradable and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is a TEM image of the silver-carbon nanoparticles described in Example 1.

[0021] Figure 2 is an XPS image of the silver-carbon nanoparticles described in Example 1.

[0022] Figure 3 These are the SEM and EDS images of the all-bagasse-based silver-carbon cling film described in Example 5.

[0023] Figure 4 This is the XPS image of the all-bagasse-based silver-carbon cling film described in Example 5.

[0024] Figure 5 This is a SEM image of the all-bagasse-based silver nanoparticle cling film described in Comparative Example 1.

[0025] Figure 6 This is the SEM image of the all-bagasse-based carbon dot cling film described in Comparative Example 2.

[0026] Figure 7 These are photos of the fresh-keeping test of the fresh-keeping films prepared in Example 5 and Comparative Examples 1-2. DETAILED DESCRIPTION

[0027] The present invention is further described by the following examples, but is not intended to be limiting of the present invention. Specific experimental conditions and methods not specified in the following examples are conventional methods commonly known to those skilled in the art.

[0028] Embodiment 1: A method for preparing silver-carbon nanoparticles, comprising the following steps: (1) adding bagasse to a sodium hydroxide solution, heating and stirring for 12 hours, filtering to obtain black liquor and filter residue, and then subjecting the black liquor to acid precipitation to obtain lignin; the pH value of the sodium hydroxide solution is 13; the acid precipitation is to add 1M sulfuric acid to the black liquor to adjust the pH value to 2, and then filtering to obtain lignin; (2) 0.2 g of lignin and 0.6 g of phenylenediamine obtained in step (1) were dissolved in an acid solution, and then placed in a polytetrafluoroethylene-lined autoclave and treated at 200° C. for 10 h, and then naturally cooled to room temperature to obtain a reaction solution; The acid solution is obtained by mixing sulfuric acid and phosphoric acid, and the volume ratio of the sulfuric acid to the phosphoric acid is 40:60; (3) The reaction solution obtained in step (2) was centrifuged at a speed of 8000 r / min for 15 min, and the supernatant was dialyzed in deionized water for 48 h, with a retention molecular weight of 1000 Da, and then dried to obtain lignin nitrogen-doped carbon dots (N-CQDs); (4) Take the lignin nitrogen-doped carbon dots obtained in step (3) and add deionized water to obtain an N-CQDs solution, then mix the N-CQDs solution with a silver nitrate solution and perform ultrasonication, and then place in an oil bath at 80°C for 12 hours to obtain a mixed solution; the volume ratio of the N-CQDs solution to the AgNO3 solution is 5:4; the concentration of the N-CQDs solution is 5 mg / mL, and the concentration of the silver nitrate solution is 1.0 mol / L; (5) The mixed solution obtained in step (4) was naturally cooled to room temperature and centrifuged at 8000 r / min for 15 min. The precipitate was dialyzed in a 1000 Da dialysis bag for 48 h and then dried at 80 °C to obtain silver-carbon nanoparticle powder. The TEM and XPS images of the obtained silver-carbon nanoparticles are shown in FIG. Figure 1 and Figure 2 , Ag 3d in AgC alone 5 / 2 and Ag3d 3 / 2 The band energies of the carbon dots are 367.6 eV and 373.6 eV respectively, and the 3d energy difference is 6 eV, which proves that the carbon dots and silver nanoparticles are successfully compounded. The silver-carbon nanoparticles are coated structures, and the carbon dots are only a few nanometers in size and are dispersed on the surface of the silver nanoparticles.

[0029] Embodiment 2: A method for preparing silver-carbon nanoparticles, comprising the following steps: (1) adding bagasse to a sodium hydroxide solution, heating and stirring for 10 hours, filtering to obtain black liquor and filter residue, and then subjecting the black liquor to acid precipitation to obtain lignin; the pH value of the sodium hydroxide solution is 13; the acid precipitation is to add 1M sulfuric acid to the black liquor to adjust the pH value to 2, and then filtering to obtain lignin; (2) 0.2 g of lignin and 0.6 g of phenylenediamine obtained in step (1) were dissolved in an acid solution, and then placed in a polytetrafluoroethylene-lined autoclave and treated at 200° C. for 10 h, and then naturally cooled to room temperature to obtain a reaction solution; The acid solution is obtained by mixing sulfuric acid and phosphoric acid, and the volume ratio of the sulfuric acid to the phosphoric acid is 40:60; (3) The reaction solution obtained in step (2) was centrifuged at a speed of 9000 r / min for 18 min, and the supernatant was dialyzed in deionized water for 48 h, with a retention molecular weight of 1000 Da, and then dried to obtain lignin nitrogen-doped carbon dots (N-CQDs); (4) Take the lignin nitrogen-doped carbon dots obtained in step (3) and add deionized water to obtain an N-CQDs solution, then mix the N-CQDs solution with a silver nitrate solution and perform ultrasonication, and then place in an oil bath at 80°C for 12 hours to obtain a mixed solution; the volume ratio of the N-CQDs solution to the AgNO3 solution is 5:4; the concentration of the N-CQDs solution is 2.5 mg / mL, and the concentration of the silver nitrate solution is 2.0 mol / L; (5) The mixed solution obtained in step (4) was naturally cooled to room temperature and centrifuged at 9000 r / min for 18 min. The precipitate was dialyzed in a 1000 Da dialysis bag for 48 h and then dried at 80 °C to obtain silver carbon nanoparticle powder.

[0030] Embodiment 3: A method for preparing silver-carbon nanoparticles, comprising the following steps: (1) adding bagasse to a sodium hydroxide solution, heating and stirring for 14 hours, filtering to obtain black liquor and filter residue, and then subjecting the black liquor to acid precipitation to obtain lignin; the pH value of the sodium hydroxide solution is 13; the acid precipitation is to add 1M sulfuric acid to the black liquor to adjust the pH value to 2, and then filtering to obtain lignin; (2) 0.2 g of lignin and 0.6 g of phenylenediamine obtained in step (1) were dissolved in an acid solution, and then placed in a polytetrafluoroethylene-lined autoclave and treated at 200° C. for 10 h, and then naturally cooled to room temperature to obtain a reaction solution; The acid solution is obtained by mixing sulfuric acid and phosphoric acid, and the volume ratio of the sulfuric acid to the phosphoric acid is 40:60; (3) The reaction solution obtained in step (2) was centrifuged at a speed of 8000 r / min for 15 min, and the supernatant was dialyzed in deionized water for 48 h, with a retention molecular weight of 1000 Da, and then dried to obtain lignin nitrogen-doped carbon dots (N-CQDs); (4) Take the lignin nitrogen-doped carbon dots obtained in step (3) and add deionized water to obtain an N-CQDs solution, then mix the N-CQDs solution with a silver nitrate solution and perform ultrasonication, and then place in an oil bath at 80°C for 12 hours to obtain a mixed solution; the volume ratio of the N-CQDs solution to the AgNO3 solution is 5:4; the concentration of the N-CQDs solution is 7.5 mg / mL, and the concentration of the silver nitrate solution is 1.5 mol / L; (5) The mixed solution obtained in step (4) was naturally cooled to room temperature and centrifuged at 8000 r / min for 15 min. The precipitate was dialyzed in a 1000 Da dialysis bag for 48 h and then dried at 80 °C to obtain silver carbon nanoparticle powder.

[0031] Embodiment 4: A method for preparing silver-carbon nanoparticles, comprising the following steps: (1) adding bagasse to a sodium hydroxide solution, heating and stirring for 15 hours, filtering to obtain black liquor and filter residue, and then subjecting the black liquor to acid precipitation to obtain lignin; the pH value of the sodium hydroxide solution is 13; the acid precipitation is to add 1M sulfuric acid to the black liquor to adjust the pH value to 2, and then filtering to obtain lignin; (2) 0.2 g of lignin and 0.6 g of phenylenediamine obtained in step (1) were dissolved in an acid solution, and then placed in a polytetrafluoroethylene-lined autoclave and treated at 200° C. for 10 h, and then naturally cooled to room temperature to obtain a reaction solution; The acid solution is obtained by mixing sulfuric acid and phosphoric acid, and the volume ratio of the sulfuric acid to the phosphoric acid is 40:60; (3) The reaction solution obtained in step (2) was centrifuged at a speed of 10000 r / min for 20 min, and the supernatant was dialyzed in deionized water for 48 h, with a retention molecular weight of 1000 Da, and then dried to obtain lignin nitrogen-doped carbon dots (N-CQDs); (4) Take the lignin nitrogen-doped carbon dots obtained in step (3) and add deionized water to obtain an N-CQDs solution, then mix the N-CQDs solution with a silver nitrate solution and perform ultrasonication, and then place in an oil bath at 80°C for 12 hours to obtain a mixed solution; the volume ratio of the N-CQDs solution to the AgNO3 solution is 5:4; the concentration of the N-CQDs solution is 10 mg / mL, and the concentration of the silver nitrate solution is 0.5 mol / L; (5) The mixed solution obtained in step (4) was naturally cooled to room temperature and centrifuged at 10000 r / min for 20 min. The precipitate was dialyzed in a 1000Da dialysis bag for 48 h and then dried at 80 °C to obtain silver carbon nanoparticle powder.

[0032] Embodiment 5: A method for preparing a full bagasse-based silver-carbon cling film, comprising the following steps: S1, take 1g of bagasse, add it to sodium hydroxide solution, heat and stir for 12h, then filter to obtain black liquor and filter residue; S2, bleaching the filter residue obtained in step S1, after bleaching, washing with deionized water, filtering until the pH is neutral, and then immersing in treatment solution A, then adding sodium hypochlorite solution, and using oil bath mode, reacting at 30° C. for 14 hours, then filtering to obtain cellulose, and storing the cellulose in deionized water to obtain 50 mL of cellulose solution for standby use; The treatment liquid A comprises the following components in parts by weight: 0.032 parts of TEMPO (2,2,6,6-tetramethylpiperidin-1-oxyl free radical), 2.2 parts of sodium chlorite, 7.5 parts of sodium phosphate, and 200 parts of deionized water; the volume ratio of the added sodium hypochlorite solution to the treatment liquid A is 1:10; The bleaching step comprises first adding glacial acetic acid to a bleaching agent to adjust the pH value to 4.6, and then placing the filter residue obtained in step (1) into the bleaching agent for bleaching, wherein the mass ratio of the filter residue to the volume ratio of the bleaching agent is 2 g:500 mL, and the bleaching agent is a sodium chlorite aqueous solution with a concentration of 1.24 g / mL; S3, taking the lignin nitrogen-doped carbon dots (N-CQDs) obtained by the preparation method described in this embodiment and adding them to deionized water to obtain an N-CQDs solution, then mixing the N-CQDs solution and the AgNO3 solution to obtain a treatment solution B, and then mixing the treatment solution B with the cellulose solution obtained in step S2, and then heating and refluxing at 80 ° C for 24 hours to obtain a feed solution; the volume ratio of the N-CQDs solution to the mass ratio of the bagasse described in step S1 is 25mL:1g, and the volume ratio of the N-CQDs solution to the AgNO3 solution is 5:4; the concentration of the N-CQDs solution is 5.0mg / mL, and the concentration of the silver nitrate solution is 1.0mol / L; S4, cooling the liquid obtained in step S3, then repeatedly filtering three times, taking the filtered residue and adding it to the treatment liquid B to react for 1 hour, then ultrasonicating for 1 hour and air drying at 40°C to obtain a full bagasse-based silver-carbon preservative film; the treatment liquid B is 100 mL of deionized water, followed by adding 70% of the mass of deionized water glycerol and 30% of the mass of deionized water formamide, and then mixing them evenly to obtain the treatment liquid B.

[0033] The test results of the obtained all-bagasse-based silver-carbon cling film are shown in Figure 3 and Figure 4 ,Depend on Figure 4 It can be seen that the Ag 3d 5 / 2 and Ag 3d 3 / 2 The band energies of the two molecules are 367.6 eV and 373.6 eV, respectively, and the 3d energy difference is 6 eV, indicating that AgNPs exist in the all-bagasse-based silver-carbon cling film. Figure 3 It can be seen that the silver carbon nanoparticles in the film are dispersed on the cellulose, where the EDS image is a mixed color image of C, N, O, and Ag, and the composite color of the C, N, and O signals in the carbon dots is coated on the surface of the white signal Ag.

[0034] Embodiment 6: A method for preparing a full bagasse-based silver-carbon cling film, comprising the following steps: S1, take 1g of bagasse, add it to sodium hydroxide solution, heat and stir for 10h, then filter to obtain black liquor and filter residue; S2, bleaching the filter residue obtained in step S1, after bleaching, washing with deionized water, filtering until the pH is neutral, and then immersing in treatment solution A, then adding sodium hypochlorite solution, and using oil bath mode, reacting at 28° C. for 15 hours, then filtering to obtain cellulose, and storing the cellulose in deionized water to obtain 50 mL of cellulose solution for standby use; The treatment liquid A comprises the following components in parts by weight: 0.030 parts of TEMPO (2,2,6,6-tetramethylpiperidin-1-oxyl free radical), 2.0 parts of sodium chlorite, 7 parts of sodium phosphate, and 180 parts of deionized water; the volume ratio of the added sodium hypochlorite solution to the treatment liquid A is 1:8; The bleaching step comprises first adding glacial acetic acid to a bleaching agent to adjust the pH value to 4.6, and then placing the filter residue obtained in step (1) into the bleaching agent for bleaching, wherein the mass ratio of the filter residue to the volume ratio of the bleaching agent is 2 g:500 mL, and the bleaching agent is a sodium chlorite aqueous solution with a concentration of 1.2 g / mL; S3, taking the lignin nitrogen-doped carbon dots (N-CQDs) obtained by the preparation method described in this embodiment and adding them to deionized water to obtain an N-CQDs solution, then mixing the N-CQDs solution and the AgNO3 solution to obtain a treatment solution B, and then mixing the treatment solution B with the cellulose solution obtained in step S2, and then heating and refluxing at 80 ° C for 12 hours to obtain a feed solution; the volume ratio of the N-CQDs solution to the mass ratio of the bagasse described in step S1 is 25mL:1g, and the volume ratio of the N-CQDs solution to the AgNO3 solution is 5:4; the concentration of the N-CQDs solution is 2.5mg / mL, and the concentration of the silver nitrate solution is 0.5mol / L; S4, cooling the liquid obtained in step S3, then repeatedly filtering three times, taking the filtered residue and adding it to the treatment liquid B to react for 1 hour, then ultrasonicating for 1 hour and air drying at 40°C to obtain a full bagasse-based silver-carbon preservative film; the treatment liquid B is 100 mL of deionized water, followed by adding 70% of the mass of deionized water glycerol and 30% of the mass of deionized water formamide, and then mixing them evenly to obtain the treatment liquid B.

[0035] Example 7: A method for preparing a full bagasse-based silver-carbon cling film, comprising the following steps: S1, take 1g of bagasse, add it to sodium hydroxide solution, heat and stir for 14h, then filter to obtain black liquor and filter residue; S2, bleaching the filter residue obtained in step S1, after bleaching, washing with deionized water, filtering until the pH is neutral, and then immersing in treatment solution A, then adding sodium hypochlorite solution, and using oil bath mode, reacting at 32° C. for 12 hours, then filtering to obtain cellulose, and storing the cellulose in deionized water to obtain 50 mL of cellulose solution for standby use; The treatment liquid A comprises the following components in parts by weight: 0.034 parts of TEMPO (2,2,6,6-tetramethylpiperidin-1-oxyl free radical), 2.4 parts of sodium chlorite, 7.8 parts of sodium phosphate, and 210 parts of deionized water; the volume ratio of the added sodium hypochlorite solution to the treatment liquid A is 1:11; The bleaching step comprises first adding glacial acetic acid to a bleaching agent to adjust the pH value to 4.6, and then placing the filter residue obtained in step (1) into the bleaching agent for bleaching, wherein the mass ratio of the filter residue to the volume ratio of the bleaching agent is 2 g:500 mL, and the bleaching agent is a sodium chlorite aqueous solution with a concentration of 1.28 g / mL; S3, taking the lignin nitrogen-doped carbon dots (N-CQDs) obtained by the preparation method described in this embodiment and adding them to deionized water to obtain an N-CQDs solution, then mixing the N-CQDs solution and the AgNO3 solution to obtain a treatment solution B, and then mixing the treatment solution B with the cellulose solution obtained in step S2, and then heating and refluxing at 80 ° C for 20 hours to obtain a feed solution; the volume ratio of the N-CQDs solution to the mass ratio of the bagasse described in step S1 is 25mL:1g, and the volume ratio of the N-CQDs solution to the AgNO3 solution is 5:4; the concentration of the N-CQDs solution is 7.5mg / mL, and the concentration of the silver nitrate solution is 1.5mol / L; S4, cooling the liquid obtained in step S3, then repeatedly filtering three times, taking the filtered residue and adding it to the treatment liquid B to react for 1 hour, then ultrasonicating for 1 hour and air drying at 40°C to obtain a full bagasse-based silver-carbon preservative film; the treatment liquid B is 100 mL of deionized water, followed by adding 70% of the mass of deionized water glycerol and 30% of the mass of deionized water formamide, and then mixing them evenly to obtain the treatment liquid B.

[0036] Embodiment 8: A method for preparing a full bagasse-based silver-carbon cling film, comprising the following steps: S1, take 1g of bagasse, add it to sodium hydroxide solution, heat and stir for 15h, then filter to obtain black liquor and filter residue; S2, bleaching the filter residue obtained in step S1, after bleaching, washing with deionized water, filtering until the pH is neutral, and then immersing in treatment solution A, then adding sodium hypochlorite solution, and using oil bath mode, reacting at 35° C. for 10 hours, then filtering to obtain cellulose, and storing the cellulose in deionized water to obtain 50 mL of cellulose solution for standby use; The treatment liquid A comprises the following components in parts by weight: 0.035 parts of TEMPO (2,2,6,6-tetramethylpiperidin-1-oxyl free radical), 2.5 parts of sodium chlorite, 8 parts of sodium phosphate, and 220 parts of deionized water; the volume ratio of the added sodium hypochlorite solution to the treatment liquid A is 1:(12; The bleaching step comprises first adding glacial acetic acid to a bleaching agent to adjust the pH value to 4.6, and then placing the filter residue obtained in step (1) into the bleaching agent for bleaching, wherein the mass ratio of the filter residue to the volume ratio of the bleaching agent is 2 g:500 mL, and the bleaching agent is a sodium chlorite aqueous solution with a concentration of 1.3 g / mL; S3, taking the lignin nitrogen-doped carbon dots (N-CQDs) obtained by the preparation method described in this embodiment and adding them to deionized water to obtain an N-CQDs solution, then mixing the N-CQDs solution and the AgNO3 solution to obtain a treatment solution B, and then mixing the treatment solution B with the cellulose solution obtained in step S2, and then heating and reflux at 80 ° C for 20 hours to obtain a feed solution; the volume ratio of the N-CQDs solution to the mass ratio of the bagasse described in step S1 is 25mL:1g, and the volume ratio of the N-CQDs solution to the AgNO3 solution is 5:4; the concentration of the N-CQDs solution is 10mg / mL, and the concentration of the silver nitrate solution is 2.0mol / L; S2, cooling the feed liquid obtained in step S3, then repeatedly filtering three times, taking the filtered residue and adding it to the treatment liquid B to react for 1 hour, and then ultrasonicating for 1 hour and air drying at 40°C to obtain a full bagasse-based silver-carbon preservative film; the treatment liquid B is 100 mL of deionized water, followed by adding 70% of the mass of deionized water glycerol and 30% of the mass of deionized water formamide, and then mixing them evenly to obtain the treatment liquid B.

[0037] Comparative Example 1: A method for preparing a whole bagasse-based silver nanoparticle (AgNPs@MC) cling film, wherein the cling film is prepared according to the method described in Example 5, but in step S3, no N-CQDs solution is used, and deionized water is used instead of N-CQDs solution to mix with AgNO3 solution to prepare treatment solution B. The SEM image of the obtained cling film is shown in Figure 5 , in which silver nanoparticles are uniformly dispersed on cellulose.

[0038] Comparative Example 2: A method for preparing a plastic wrap made of all bagasse-based carbon dots (N-CQDs@MC), wherein the plastic wrap is prepared according to the method described in Example 5, but in step S3, no AgNO3 solution is used, and deionized water is used instead of AgNO3 solution to mix with the N-CQDs solution to prepare the treatment solution B. The SEM image of the obtained plastic wrap is shown in Figure 6 Since the carbon dots are only a few nanometers in size, no particles can be seen in this scan image.

[0039] Experimental Example: Prepare a cling film according to the method described in Example 5 and Comparative Examples 1-2, and then use the cling film to preserve mandarin oranges. The test results are shown in Figure 7 .

[0040] The mandarin oranges treated with the all-bagasse-based silver-carbon cling film prepared in Example 5 of the present invention have the longest storage time, and there is no bacterial infection on the outside, which confirms the efficient and long-lasting antibacterial properties of the AgC@MC film. In contrast, the single all-bagasse-based silver nanoparticle film (Comparative Example 1) and the all-bagasse-based carbon dot film (Comparative Example 2) do not have long-term antibacterial properties and cannot keep the fruit fresh for a long time. Therefore, the "bayberry hanging branch" bionic structure of the AgC@MC obtained by the present invention, the dual fixation effect of AgC@MC, and the synergistic light-responsive antibacterial of the carbon dots give the composite film a unique long-term fresh-keeping performance.

[0041] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing silver-carbon nanoparticles, characterized in that: The following steps are involved: (1) Add bagasse to sodium hydroxide solution, heat and stir for 10-15 hours, filter to obtain black liquor, and then acidify the black liquor to obtain lignin; (2) dissolving the lignin and phenylenediamine obtained in step (1) in an acid solution, placing the mixture in a polytetrafluoroethylene-lined autoclave, treating the mixture at 200° C. for 10 h, and then cooling the mixture naturally to room temperature to obtain a reaction solution; The acid solution is obtained by mixing sulfuric acid and phosphoric acid, and the volume ratio of the sulfuric acid to the phosphoric acid is 40:60; (3) After centrifuging the reaction solution obtained in step (2), the supernatant was dialyzed in deionized water for 48 hours to retain a molecular weight of 1000 Da, and then dried to obtain lignin nitrogen-doped carbon dots; (4) taking the lignin nitrogen-doped carbon dots obtained in step (3) and adding deionized water to obtain an N-CQDs solution, then mixing the N-CQDs solution with a silver nitrate solution and ultrasonicating the mixture, and then placing the mixture in an oil bath at 80° C. for 12 h to obtain a mixed solution; (5) The mixed solution obtained in step (4) was naturally cooled to room temperature and then centrifuged. The precipitate was dialyzed in a 1000Da dialysis bag for 48 hours and then dried at 80 °C to obtain silver carbon nanoparticle powder.

2. The method for preparing silver-carbon nanoparticles according to claim 1, characterized in that: The pH value of the sodium hydroxide solution in step (1) is 13.

3. The method for preparing silver-carbon nanoparticles according to claim 1, characterized in that: The acid precipitation in step (1) is to add 1M sulfuric acid to the black liquor to adjust the pH value to 2, and then filter to obtain lignin.

4. The method for preparing silver-carbon nanoparticles according to claim 1, characterized in that: In step (3) and step (5), the centrifugation is carried out at a speed of 8000 to 10000 r / min for 15 to 20 min.

5. The method for preparing silver-carbon nanoparticles according to claim 1, characterized in that: In step (4), the volume ratio of the N-CQDs solution to the AgNO3 solution is 5:4; the concentration of the N-CQDs solution is 2.5-10 mg / mL, and the concentration of the silver nitrate solution is 0.5-2.0 mol / L.

6. A method for preparing a full bagasse-based silver-carbon cling film, characterized in that: The following steps are involved: S1, taking bagasse, adding it to sodium hydroxide solution, heating and stirring for 10-15h, and then filtering to obtain black liquor and filter residue; S2, bleaching the filter residue obtained in step S1, and then immersing it in treatment solution A, then adding sodium hypochlorite solution, and using oil bath method, reacting at 28-35° C. for 10-15 hours, then filtering to obtain cellulose, and storing the cellulose in deionized water to obtain a cellulose solution for standby use; The treatment liquid A comprises the following components in parts by weight: 0.030-0.035 parts of TEMPO, 2.0-2.5 parts of sodium chlorite, 7-8 parts of sodium phosphate, and 180-220 parts of deionized water; the volume ratio of the added sodium hypochlorite solution to the treatment liquid A is 1:(8-12); S3, adding the lignin nitrogen-doped carbon dots obtained by the preparation method as described in claims 1 to 5 to deionized water to obtain an N-CQDs solution, then mixing the N-CQDs solution with an AgNO3 solution to obtain a treatment solution B, then mixing the treatment solution B with the cellulose solution obtained in step S2, and then heating and refluxing at 80 ° C for 12 to 24 hours to obtain a feed solution; the volume ratio of the N-CQDs solution to the mass ratio of the bagasse in step S1 is 25 mL: 1 g, and the volume ratio of the N-CQDs solution to the AgNO3 solution is 5:4; S4, cooling the liquid obtained in step S3, then repeatedly filtering three times, taking the filtered residue and adding it to the treatment liquid B to react for 1 hour, and then ultrasonicating for 1 hour and then air-drying at 40°C to obtain a full bagasse-based silver-carbon preservative film; the treatment liquid B is obtained by mixing glycerol, formamide and deionized water.

7. The method for preparing the full bagasse-based silver-carbon cling film according to claim 6, characterized in that: In step S2, the concentration of the N-CQDs solution is 2.5 to 10 mg / mL, and the concentration of the silver nitrate solution is 0.5 to 2.0 mol / L.

8. The method for preparing the full bagasse-based silver-carbon cling film according to claim 6, characterized in that: The bleaching in step S2 is to first add glacial acetic acid to a bleaching agent to adjust the pH value to 4.6, and then put the filter residue obtained in step (1) into the bleaching agent for bleaching, wherein the mass ratio of the filter residue to the volume of the bleaching agent is 2g:500mL, and the bleaching agent is a sodium chlorite aqueous solution with a concentration of 1.2-1.3g / mL.

9. The method for preparing the full bagasse-based silver-carbon cling film according to claim 6, characterized in that: After bleaching, the filter residue in step S2 is rinsed with deionized water and filtered until the pH is neutral.

10. The method for preparing the silver carbon fiber cling film according to claim 6, characterized in that: In step S3, the mass ratio of glycerol to formamide in the treatment solution B is 7:3.